DIRECTIVE SPEECH ACTS AMONG THE MEMBERS OF STUDENT EXECUTIVE BOARD IN SURAKARTA - Muttaqin, Wildan Mahir (Universitas Islam Negeri Raden Intan Lampung, 2018)
The study is aimed to describes the type of directive speech act among the the members of student executive board and some factors happened in the formal situation. There are some relation between speaker, hearer and utterances based on context. The data were taken using observation and interview. The observation was done by recording the discussion on the formal meeting. In addition, the interview was required to complete the data by giving some questions on the list. The the data were classified based on types of speech act from Searle. The finding shows many types of directive speech act produced by university students were caused by some factors, such as age and gender. The researcher also identified the active and passive speakers in this situation. Asking and checking were the most occured on directive speech act while forbiding was less occured on it.Keywords: speech act, directive speech act, communication.